Systematic Screening for Perinatal Mood and Anxiety Disorders to Promote Onsite Mental Health Consultations: A Quality Improvement Report. (24th May 2021) - Johnson, Amber; Stevenson, Eleanor; Moeller, Loralie; McMillian‐Bohler, Jacquelyn
Abstract : Introduction: Perinatal mood and anxiety disorders are the most common complication during pregnancy and postpartum. Screening, diagnosis, and treatment for these disorders are inhibited by limited mental health resources for patients and health care providers, lack of provider training, and time constraints. Systematic screening combined with onsite mental health consultation is an evidence‐based method to increase timely diagnosis and treatment. The purpose of this quality improvement project was to promote and improve onsite mental health consultations through the implementation of a systematic screening guideline. Process: The systematic screening guidelines included administration of the Patient Health Questionnaire‐9 at the perinatal intake visit, the Edinburgh Perinatal Depression Scale between 28 and 32 weeks' gestation and again between 2 and 8 weeks postpartum. The guidelines included onsite mental health consultations for eligible women. Screening rates, attended onsite mental health consultations, and health care provider satisfaction and feedback surveys were collected over a 3‐month period, before and after guideline implementation. Outcomes: Perinatal mood and anxiety disorder screening rates were significantly increased from 24.9% to 64.2% ( P < .001) at the perinatal intake visit and in the third trimester from 0.3% to 32.8% ( P < .001) with the implementation of a systematic screening guideline. Onsite mental health consultations significantly increased from 7.2% to 15.2% ( P < .001). Perinatal care providers (n = 9, 100%) were satisfied with the screening guideline and reported that it added 5 minutes or less to their office visits. Discussion: The implementation of a systematic perinatal mood and anxiety disorder screening guideline increased completed screenings in the perinatal period and increased the number of attended onsite mental health consultations. Systematic screening combined with onsite mental health consultation is a successful way to identify at‐risk women and offer critical and convenient maternal mental health care without increasing the burden on perinatal care providers.